2018
DOI: 10.1159/000490462
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chorionicity on Maternal Cardiac Adaptation to Uncomplicated Twin Pregnancy: A Prospective Longitudinal Study

Abstract: Objective: The objective of this study was to longitudinally evaluate maternal echocardiographic findings in uncomplicated twin gestations according to chorionicity. Methods: Healthy women with twin pregnancy were assessed with transthoracic echocardiography across the first, second, and third trimesters. Cardiac findings were compared within each group and between monochorionic (MC) and dicho­rionic (DC) pregnancies. Results: Overall, 19 MC and 48 DC uncomplicated twin pregnancies were included. In the MC gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
3
19
1
Order By: Relevance
“…Ghi et al reported that monochorionic twin pregnancies recognized lower CO, higher systemic vascular resistance, and higher E/A compared to dichorionic twin pregnancies [32], but we found no differences in echocardiographic parameters and cardiac biomarkers between the monochorionic and dichorionic twin pregnancies in our study ( Table 5). This result may also be associated with sample size issues, further investigation is warranted.…”
Section: Discussioncontrasting
confidence: 74%
“…Ghi et al reported that monochorionic twin pregnancies recognized lower CO, higher systemic vascular resistance, and higher E/A compared to dichorionic twin pregnancies [32], but we found no differences in echocardiographic parameters and cardiac biomarkers between the monochorionic and dichorionic twin pregnancies in our study ( Table 5). This result may also be associated with sample size issues, further investigation is warranted.…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, chorionicity did not seem to affect any hemodynamic parameter. In another recent study using echocardiography, longitudinal changes in maternal hemodynamics were of smaller magnitude in monochorionic than in dichorionic twin pregnancies, 29 possibly because of a smaller increase in the circulating volume.…”
Section: Discussionmentioning
confidence: 85%
“…However, this trend was not observed in women with twin pregnancies because of the limited sample size and because catecholamine production from postoperative pain affected BNP, considering that 95% of women had undergone cesarean section [34]. We found two reports of hemodynamic comparison between monochorionic and dichorionic twin pregnancies [18,35]. Ghi et al reported that monochorionic twin pregnancies had lower cardiac output, higher systemic vascular resistance, and higher E/A than dichorionic twin pregnancies [35], but our study found no differences in echocardiographic parameters and cardiac biomarkers between monochorionic and dichorionic twin pregnancies (Table 5), as in the results of Orland et al [18].…”
Section: Discussionmentioning
confidence: 90%
“…We found two reports of hemodynamic comparison between monochorionic and dichorionic twin pregnancies [18,35]. Ghi et al reported that monochorionic twin pregnancies had lower cardiac output, higher systemic vascular resistance, and higher E/A than dichorionic twin pregnancies [35], but our study found no differences in echocardiographic parameters and cardiac biomarkers between monochorionic and dichorionic twin pregnancies (Table 5), as in the results of Orland et al [18]. Ghi et al [35] attributed the difference to the lower circulating blood volume of the monochorionic twin pregnancies, compared with that of the dichorionic twin pregnancies, but our study had no data to complement their findings.…”
Section: Discussionmentioning
confidence: 99%